The effect of giving ambon bananas during the first stage of labor on the duration of the second stage of labor - Yeyen Putriana; Risneni Risneni; Eva Berliana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: During the intrapartum period, a laboring mother experiences physiological stress due to contractions of the uterine muscles and skeletal muscles. Continuous contractions during the first stage of labor for 8 to 10 hours require adequate energy. Pain caused by these contractions often leads to a decreased appetite and fluid intake in laboring mothers, resulting in insufficient energy when entering the second stage of labor. This lack of energy can reduce the strength of uterine contractions, which may prolong the duration of the second stage of labor. Bananas are known as a source of carbohydrates and potassium that are easily available and can be given to laboring mothers as an energy reserve as well as to maintain electrolyte balance. Purpose: To determine the difference in the duration of the second stage of labor between laboring mothers who were given bananas during the first stage of labor and those who were not. Method: This study used a quasi-experimental design. The study population consisted of all laboring mothers at PMB Nurhidayah, located in Ketibung District, South Lampung Regency, in 2024. Samples were selected based on inclusion and exclusion criteria. A total of 40 respondents were included, consisting of 20 in the intervention group and 20 in the control group. The intervention group was given two bananas weighing a total of 400 grams during the first stage of labor. The duration of the second stage of labor was then measured in minutes. Data analysis was conducted using the Independent T-test. Results: There was no difference in the duration of the second stage of labor between mothers who were given bananas and those who were not, with a p-value> 0.05. Conclusion: The administration of bananas during the first stage of labor did not affect the duration of the second stage of labor. Suggestion: Further research is needed to explore other benefits of bananas beyond their effect on the duration of the second stage of labor, such as fatigue levels and muscle strength.